ChemInform Abstract: Enantioselective Synthesis of 2‐Arylbicyclo[1.1.0]butane Carboxylates. Issue 23 (16th May 2013) - Qin, Changming; Davies, Huw M. L.
Abstract A highly diastereoselective synthesis of both 2‐arylbicyclo[1.1.0]butane carboxylates (II) and cyclohexene derivatives (III) via dirhodium‐catalyzed decomposition of α‐allyldiazoesters is developed.